2020
DOI: 10.1088/2053-1591/abd33d
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and photocatalytic activity using SiO2-TiO2 nanocomposites under UV light

Abstract: SiO2-TiO2 nanocomposites were synthesized by the sol-gel method with different SiO2 contents (0.125, 0.25, 0.50 and 0.75%wt). The characteristics of prepared samples were obtained from x-ray diffractometer (XRD), field emission scanning electron microscope (FESEM), UV–visible spectrophotometer, and Brunauer Emmett and Teller (BET) surface area analyzer. SiO2-TiO2 nanocomposites have higher UV absorption capability and a higher specific surface area compared to pure TiO2, resulting in improved dye degradation b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…The organic component is then broken down by this hydroxyl radical (OH*) into water (H2O) and carbon dioxide (CO2). [9] As per the above literature review, in the present work, it was reported that Nanocomposite of TiO2/ SiO2 was synthesized by the co-precipitation Method i.e. wet chemical precipitation Method.…”
Section: Introductionmentioning
confidence: 70%
“…The organic component is then broken down by this hydroxyl radical (OH*) into water (H2O) and carbon dioxide (CO2). [9] As per the above literature review, in the present work, it was reported that Nanocomposite of TiO2/ SiO2 was synthesized by the co-precipitation Method i.e. wet chemical precipitation Method.…”
Section: Introductionmentioning
confidence: 70%
“…A modified sol–gel method was used for the synthesis of SiO 2 –TiO 2 NC 42 . TTIP solution was first prepared by adding 9 mL of TTIP in 100 mL of absolute ethanol.…”
Section: Methodsmentioning
confidence: 99%
“…A modified sol-gel method was used for the synthesis of SiO 2 -TiO 2 NC. 42 TTIP solution was first prepared by adding 9 mL of TTIP in 100 mL of absolute ethanol. After this, dried SiO 2 NPs were added to the solution with a 0.75% weight to volume ratio.…”
Section: Synthesis Of Sio 2 -Tio 2 Nanocompositementioning
confidence: 99%
“…Ternary magnetic photocatalytic GO composites have been investigated for the photodegradation of dyes (methylene blue, rhodamine B, methyl orange, crystal violet, tartrazine and malachite green). Although the most common configuration of the nanocomposite consists of graphene oxide layers decorated with magnetite (Fe 3 O 4 ) and titania (TiO 2 ) nanoparticles [ 87 , 88 , 89 , 90 , 91 , 92 , 93 ]; other morphologies have been explored, such as: core/shell Fe 3 O 4 @TiO 2 nanoparticles on graphene oxide [ 94 , 95 , 96 , 97 ]; core/shell Fe 3 O 4 @SiO 2 + TiO 2 nanoparticles on graphene oxide [ 98 ], and graphene sheets wrapping Fe 3 O 4 and TiO 2 nanoparticles in a sort of nanocapsule [ 99 ]; a schematic summary of these morphologies is presented in Figure 6 . Coprecipitation is a widely used technique to synthesize inorganic nanoparticles; two or more water soluble salts react in aqueous solution to form a water insoluble salt that precipitates and forms nanoparticles.…”
Section: Ternary Nanocomposites Go/tio 2 /Xmentioning
confidence: 99%
“… Schematic representations of the different configurations reported in the literature for ternary nanocomposites of graphene oxide, magnetite nanoparticles (Fe 3 O 4 ) and titania nanoparticles (TiO 2 ) [ 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 ]. …”
Section: Figurementioning
confidence: 99%